Individual caries increments during adolescence in seven Norwegian cohorts born 1996–2002 - Hedda Høvik; Knut Helge Midtbø Jensen; Torunn Børsting; Randi Krog Eftedal; Göran Dahllöf; Bjørnar Hafell; Tone Natland Fagerhaug; Eva Lassemo; Marikken Høiseth; Abhijit Sen; Marit S. Skeie (BMC Oral Health)
Abstract Background Caries increment during adolescence, including enamel caries, is rarely explored in detail. This study assessed the caries increment during the period from 12 to 18 years. The specific objectives were to examine time trends, increment variability between individuals, and whether baseline caries experience at 12 years or sex had an impact on the caries increment. Methods The sample included seven birth cohorts (1996–2002; n = 23,135) from a general adolescent population in Trøndelag County, Norway. Data was based on dental records from the Public Dental Service. Two caries increment thresholds were examined at the tooth level: the enamel caries increment (ΔD1–2T), and the caries increment at the dentin level, including missing and filled teeth (ΔD3–5MFT). Zero-inflated Poisson models were used to account for the skewed distribution with a high proportion of zero caries increment (31.1% with ΔD1–2T = 0 and 33.4% with ΔD3–5MFT=0). Results The mean caries increments for the seven cohorts were ΔD1–2T = 3.14 (95% CI: 3.09–3.19) and ΔD3–5MFT = 2.51 (95% CI: 2.47–2.55). A modest temporal trend of decreasing caries increment across cohorts was observed at both thresholds: ΔD1–2T = -0.31 (95% CI: ±0.13) and ΔD3–5MFT = -0.43 (95% CI: ±0.11). However, this decrease was small compared to the variation in caries increments between individuals. Females had slightly lower mean caries increment than males, but there was no effect of sex on the change across cohorts. Adolescents with high baseline caries experience at 12 years had higher mean caries increments compared to the intermediate or low baseline caries experience groups, and a reduction across cohorts was only seen in the two latter groups. Conclusions While there was a modest reduction in caries increment across cohorts, this reduction was small compared to the variation in caries increments between individuals. The change across cohorts was the same in females and males. Baseline caries experience at 12 years was a strong predictor of caries increment and the reduction across cohorts was only seen among those with lower baseline caries experience, incdicating an increased dental health disparity among Norwegian adolescents. Clinical Trial Registration ClinicalTrials.gov ID: NCT05935813, Release Date: 28/06/2023.